Nanoparticles that stimulate the production and quality of cucumber fruits (Cucumis sativus L.) - Reyes-Perez, Juan; Ramos-Remache, Rommel; Jerez , Eduardo; Nazareno-Ortiz, René; Murillo-Noboa, Kevin; García- Hernández, José; Márquez-Guerrero, Selenne (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Due to the high consumption of cucumber (Cucumis sativus L.) and its economic importance, improving resource efficiency is a priority to maximize yields. The combination of silicon oxide (SiO2), chitosan, and micronutrients are beneficial for plant growth and development. The objective of this study was to determine the influence of micronutrient- provided SiO2 nanoparticles encapsulated in a chitosan gel on the growth, yield, and quality of cucumber fruits. The study was conducted in a cultivation house, where three concentrations of silicon nanoparticles and a control were evaluated in a randomized block design with four replicates. Plant growth (height and stem diameter), days to flowering, number of fruits per plant, yield, and fruit quality were evaluated. Foliar application of Si-NPs promoted greater plant growth at the highest concentration (2,000 mg.L-1), as well as improved the nutraceutical quality of cucumber fruits by increasing the contents of antioxidants, flavonoids, phenols and total soluble solids.